Characterization of methylcellulose produced from sugar cane bagasse cellulose: Crystallinity and thermal properties - Rodrigues Filho, Guimes; de Assuncao, Rosana M. N.; Vieira, Julia G.; Meireles, Carla da S.; Cerqueira, Daniel A.; da Silva Barud, Hernane; Ribeiro, Sidney José Lima [UNESP]; Messaddeq, Younes [UNESP] (Elsevier B.V., 2007)
In the present work, methylcellulose produced from sugar cane bagasse was characterized by FTIR, WAXD, DTA and TGA techniques. Two samples were synthesized: methylcellulose A and rnethylcellulose B. The only difference in the process was the addition of fresh reactants during the preparation of methylcellulose B. The ratio between the absorption intensities of the C-H stretching band at around 2900 cm(-1) and C-H stretching at around 3400 cm(-1) for methylcellulose B is higher than for methylcellulose A, indicating that methylcellulose B showed an increase in the degree of substitution (DS). Methylcellulose A presents a more heterogeneous structure, which is similar to the original cellulose as seen through FTIR and DTA. Methylcellulose B showed thermal properties similar to commercial methylcellulose. The modification of rnethylcellulose preparation method allows the production of a material with higher DS, crystallinity and thermal stability in relation to the original cellulose and to methylcellulose A. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: sugar cane bagasse; methylcellulose; FTIR; WAXD; DTA/TG